IKLIM KOMUNIKASI ORGANISASI - Muspawi, Mohamad; Mika, Mika; Viola, Mayshel Adinda; Karmila, Karmila (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2023)
This study discusses the organizational communication climate. The purpose of this study is to be able to find out what is included in the scope of organizational communiction climate, which wiil then be described and explained in more detail. The method used in this study is aqualitative method with a literature study approach, while the literature used is by utilizing digital litecary and other data that contains the objct under study. The results of the research show that the organization is so important for human life and civilization in living theirdaily lives for fulfill their needs and desires, therefore it is very impotant for us to understand the organizational communication climate, so that formation and implementation of the organization formed can be done as well as possible. Furthermore, the main topic discussion in this study is the definition and concept of organizational communication climate, factors that influence organizational communication climate, the impact of organizational communication climate on organizational performance, improving organizational communication climate, and case studies or examples. Â  Key Words: Organizational, Communication, Climate